Civil Lawsuit Cases of Forest and Land Fires PT Kalista Alam (Study of Meulaboh District Court Decision Number 12/PDT.G/2012/PN.MBO) - Ikhsana, Lisa; Rahmah, Nabilla Alya (Universitas Negeri Semarang, 2021)
Cases of forest fires in Indonesia are sometimes caused by human activities. Land clearing is often a reason to let up a lawsuit. The Ministry of Environment and Forestry (KLHK) has made every effort as a form of anticipation and to overcome cases of forest and land fires (karhutla) in Indonesia. One of the countermeasures is the filing of a civil lawsuit to the perpetrators of the karhutla. PT Kalista Alam as an example of various palm oil companies that are the target of civil lawsuits by the Ministry of Environment and Forestry over forest fires. The lawsuit is based on how much of an impact it has on various aspects, both from legal, environmental, and materiil aspects. This research uses quantitative research methods that are with a systematic normative juridical legal approach. There will be further explanations about the unlawful actions of forest and land fires committed by PT Kalista Alam in Aceh based on the perspective of civil law.